2015
DOI: 10.1021/acs.chemmater.5b02177
|View full text |Cite
|
Sign up to set email alerts
|

Porous Two-Dimensional Nanosheets Converted from Layered Double Hydroxides and Their Applications in Electrocatalytic Water Splitting

Abstract: Porous materials are of particular interest due to their high surface area and rich edge sites, which are favorable for applications such as catalysis. Although there are well-established strategies for synthesizing porous metal oxides (e.g. by annealing the corresponding metal hydroxides), facile and scalable routes to porous metal hydroxides and metal chalcogenides are lacking. Here, we report a simple and general strategy to synthesize porous nanosheets of metal hydroxides by selectively etching layered dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
180
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(192 citation statements)
references
References 57 publications
10
180
0
Order By: Relevance
“…As seen in Figure 3a,t he CF substrate has an egligible HER performance with af eatureless polarization curve.N otably, the Se-rich NiSe 2 -450 electrode achieved acurrent density of 10 mA cm À2 at al ow overpotential of 117 mV (h 10 ), which is lower than those recently reported for other binary pyrite structures. [13,26] This electrode demonstrates the best HER catalytic performance among all synthesized samples,with h 10 values of 125 mV and 129 mV for NiSe 2 -400 and NiSe 2 -500, respectively ( Figure S9). In an attempt to explore these differences between the as-grown NiSe 2 based samples,t he double-layer capacitances (C dl )w ere utilized to estimate the effective electrochemically active area of the solid-liquid interface (Note SIII, Figures S10 a-c and 11 a).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…As seen in Figure 3a,t he CF substrate has an egligible HER performance with af eatureless polarization curve.N otably, the Se-rich NiSe 2 -450 electrode achieved acurrent density of 10 mA cm À2 at al ow overpotential of 117 mV (h 10 ), which is lower than those recently reported for other binary pyrite structures. [13,26] This electrode demonstrates the best HER catalytic performance among all synthesized samples,with h 10 values of 125 mV and 129 mV for NiSe 2 -400 and NiSe 2 -500, respectively ( Figure S9). In an attempt to explore these differences between the as-grown NiSe 2 based samples,t he double-layer capacitances (C dl )w ere utilized to estimate the effective electrochemically active area of the solid-liquid interface (Note SIII, Figures S10 a-c and 11 a).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Then, it can be aged and converted to anhydrous β-Ni(OH)2 in base or in vacuum environment 209 . Wang et al 211 demonstrated a new strategy to synthesize β-Ni(OH)2 from NiGa LDH nanoplate precursors by selective etching away Ga 3+ ions, which was further converted to NiSe2 by a solution method. Generally, β-NiOOH shows better electrocatalytic activity than γ-NiOOH.…”
Section: Nickle-based Oer Catalystsmentioning
confidence: 99%
“…In this context, considerable research efforts have recently been de-voted to the search for efficient and inexpensive OER catalysts comprising earth-abundant elements, including transitionmetal oxides, [8][9][10] hydroxides, [11][12][13] perovskites, [14,15] phosphates, [16,17] sulfides, [18,19] and recently reported phosphides. [33][34][35][36][37][38][39][40] For example, Stern and Hu compared the OER performance of bulk Ni(OH) 2 films to that of Ni(OH) 2 nanoparticles and found that the Ni(OH) 2 nanoparticles only neededasmall overpotential (h)o f3 00 mV to deliver ac urrent density of 10 mA cm À2 (h 10 ), and thus, they substantially outperformed bulk Ni(OH) 2 films and demonstratedt he benefito fn anostructuring. Previous work on the OER performance of Ni(OH) 2 was primarily focusedo ne lectrodepositeda nd physically depositedt hin films.…”
Section: Introductionmentioning
confidence: 99%